A numerical investigation on flow past skewed vortex generators ahead of a backward facing ramp - Cheawchan, Atcha-uea (2022)
Flow past a backward facing ramp (BFR) with rectangular vane-type vortex generators (VGs) located upstream has been studied numerically using OpenFOAM based steady-state RANS simulations. In particular, single and multiple pair(s) of boundary layer height VGs are skewed at 10° and 30° to study their effects on the flow separation behaviour at Re=3×106. Streamwise and cross-stream results show that single VGs produce counter-rotating streamwise vortices with increasingly different vortex-core strengths and vortical interactions when skewness angle increases. At 30° however, co-rotating vortices are formed instead with significantly heightened vortical interaction levels, leading to asymmetric flow separation and reattachment behaviour. In particular, the use of multiple VGs under the same condition further accentuate these behaviour and results in significant changes to the wall shear stress distribution. Clarifications on how the flow separation region is distorted by the symmetric/asymmetric streamwise vortices based on velocity component analysis are also provided. Lastly, trajectories of the streamwise vortices and vortex-core characteristics support the notion that the streamwise vortices behave significantly more non-linearly at 30° skewness angle here, and that skewing the present VGs such that they produce co-rotating vortices instead of counter-rotating ones leads to very different flow separation control characteristics.